Hubungan Umur dan Frekuensi Hubungan Seksual pada Menopause di Desa Purbayasa Kecamatan Padamara Kabupaten Purbalingga - Isnaeni, Siti; Kumalasari, Retno (JURNAL KESEHATAN TERAPAN, 2025)
Biological changes experienced by women during menopause can affect various aspects of life, including sexual activity. One of the key factors to examine is the relationship between age and sexual frequency in menopausal women. This study aims to investigate the correlation between age and the frequency of sexual activity among menopausal women in Purbayasa Village, Padamara Subdistrict, Purbalingga Regency. This research employed a correlational analytic design with a cross-sectional approach involving 118 female respondents aged 40–64 years who met the inclusion criteria. The sampling technique used was purposive sampling, and data analysis was conducted using the chi-square test. The results showed that most women in the menopausal age group remained sexually active, with a frequency of ≥2 times per week (57.8%). In contrast, only 23.1% of postmenopausal women reported similar activity levels. The statistical test revealed a significant relationship between age and sexual frequency (p = 0.000; CC = 0.442), indicating a moderate association. The study concludes that as age increases, the frequency of sexual activity in menopausal women tends to decrease. This decline is influenced not only by hormonal changes but also by psychological, physical, and partner-related factors. Therefore, attention to the sexual health of menopausal women should be an integral part of comprehensive health services to support their overall quality of life.